2020
DOI: 10.28955/alinterizbd.739372
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phenolic Content, Antioxidant Properties and Antimicrobial Activity of Flower and Leaf Extracts from Some Hypericum Species Affected by Wild Habitat Altitude

Abstract: In this study, determination of habitat altitude effect on the total phenolic contents, antioxidant and antimicrobial activities of flower and leaf extracts from Hypericum montbretii, H. orientale and H. perforatum species was aimed. The plants were collected randomly from forages (altitudes were ranged from 430 to 1105 m a.s.l.) located in Western Black Sea Region, Turkey. Antioxidant properties of ethanolic extracts were determined with DPPH and ABTS assay and antimicrobial activities of the extracts on Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…indicates that the hypericin could reduce oral bacteria that produce acid, suggesting it could be used as an appropriate and safe alternative to mouthwashes and oral disinfectants (Khadem Nezhad et al, 2017). Özdemir et al (2020) reported that H. perforatum L. flower and leaf extracts exhibited a broad antibacterial spectrum against B. subtilis NRRL B‐209, B. licheniformis NRRL‐B‐1001, B. cereus NRRL B‐3711, Bacillus pumilis NRRL BD‐142, Staphylococcus aureus ATCC 33862, P. aeruginosa ATCC 27853, L. monocytogenes ATCC 7644, and Listeria inocua ATCC 33090; however, they were ineffective against E. coli ATCC 25922.…”
Section: Pharmacological Properties Of H Perforatum L Associated With...mentioning
confidence: 99%
“…indicates that the hypericin could reduce oral bacteria that produce acid, suggesting it could be used as an appropriate and safe alternative to mouthwashes and oral disinfectants (Khadem Nezhad et al, 2017). Özdemir et al (2020) reported that H. perforatum L. flower and leaf extracts exhibited a broad antibacterial spectrum against B. subtilis NRRL B‐209, B. licheniformis NRRL‐B‐1001, B. cereus NRRL B‐3711, Bacillus pumilis NRRL BD‐142, Staphylococcus aureus ATCC 33862, P. aeruginosa ATCC 27853, L. monocytogenes ATCC 7644, and Listeria inocua ATCC 33090; however, they were ineffective against E. coli ATCC 25922.…”
Section: Pharmacological Properties Of H Perforatum L Associated With...mentioning
confidence: 99%